Rediscovery of Liara (Unalianus) heteracanthus (Redtenbacher, 1891) (Orthoptera: Tettigoniidae: Conocephalinae: Agraeciini) from India with notes on its distribution - Kumar, Hirdesh; Kushwaha, Sandeep; Chand, D. Suresh (Zootaxa, 2021)
More than one hundred years after its description, a male specimen of Liara (Unalianus) heteracanthus (Redtenbacher, 1891) was collected at a new locality in the Mizoram State, India. Opportunity is taken to redescribe and illustrate this specimen.